Audit market competition: causes and consequences - Muhamad Sori, Zulkarnain (ICFAI University Press, 2009)
The aim of this paper is to examine the impact of competition in audit market and client importance to perceived auditor independence from the perspective of Malaysian auditors, loan officers and senior managers of public listed companies. It is found that auditor independence would be threatened if auditors were to receive significant fees from a single client. The dependence on a single client would cause auditor to face a 'self-threat' risk, where they were economically and financially reliant on a single customer. The interview survey disclosed that regulatory authorities should closely monitor the profession by persistently scrutinising each audit firm's revenue and expenses.